2014
DOI: 10.2174/1573395509666131217000000
|View full text |Cite
|
Sign up to set email alerts
|

Role of Chemokines and Trafficking of Immune Cells in Parasitic Infections

Abstract: Parasites are diverse eukaryotic pathogens that can have complex life cycles. Their clearance, or control within a mammalian host requires the coordinated effort of the immune system. The cell types recruited to areas of infection can combat the disease, promote parasite replication and survival, or contribute to disease pathology. Location and timing of cell recruitment can be crucial. In this review, we explore the role chemokines play in orchestrating and balancing the immune response to achieve optimal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 154 publications
0
28
0
Order By: Relevance
“…During helminth infections, parasites develop inflammatory responses, regulated primarily by chemokines or cytokines. The recruitment of effector cells (leukocytes, eosinophils and lymphocyte) to the site of infection and their functions serve for disease control [60]. Gastrointestinal nematodes could actively stimulate cell migration to the target area of infection resulting in inflammation, favorable for parasite existence [46].…”
Section: Discussionmentioning
confidence: 99%
“…During helminth infections, parasites develop inflammatory responses, regulated primarily by chemokines or cytokines. The recruitment of effector cells (leukocytes, eosinophils and lymphocyte) to the site of infection and their functions serve for disease control [60]. Gastrointestinal nematodes could actively stimulate cell migration to the target area of infection resulting in inflammation, favorable for parasite existence [46].…”
Section: Discussionmentioning
confidence: 99%
“…Despite being two different parasites belonging to the same family, they display an utterly distinct morphological and biobehavior which requests the different modality and results in different prognosis [ 13 ]. Like other parasitic infections, immune responses are now known to play a crucial role in the progress of disease development [ 14 , 15 ]. During the long-term E. granulosus / E. multilocularis host interaction, the parasite has evolved a broad spectrum of abilities to modulate the host's immune system [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Upon parasite entry in the small intestine, infected enterocytes secrete chemokines such as (CXCL2), which initially recruit Ly6G + neutrophilic granulocytes to the site of infection . Neutrophils play an important role in protection against infections by phagocytosis and secretion of effector molecules such as IL‐12, IL‐1β, TNF, CXCL1 and CXCL2, activating other immune cell subsets.…”
Section: Immune Response To Toxoplasma Gondiimentioning
confidence: 99%
“…Upon parasite entry in the small intestine, infected enterocytes secrete chemokines such as (CXCL2), which initially recruit Ly6G + neutrophilic granulocytes to the site of infection. 26 Neutrophils play an important role in protection against infections by phagocytosis and secretion of effector molecules such as IL-12, IL-1β, TNF, CXCL1 and CXCL2, activating other immune cell subsets. However, we have previously shown that specific depletion of Ly6G + neutrophil granulocytes in the acute phase of the infection did not affect parasite control in wild-type mice, suggesting their complementary role in host defence.…”
Section: And Ilcs the Contribution Of Ilcs Vs Th Cells In Various DImentioning
confidence: 99%